Effectiveness of a Mobile Application Empowerment Educational Program on Nurses’ Attitudes and Competencies in Patient Safety - Banjarnahor, Seriga; Simatupang, Lenny L.; Anggriani, Theresia; Sinaga, Regina M.; Harahap, Sridama Y.; Handoko, Erwin (Poltekkes Kemenkes Surabaya, 2025)
Patient safety is a global issue that must be prioritized in health care facilities, Patient Safety Incidents often occur and one of the causes is human error from health workers, therefore it is important to improve the quality of Human Resources, especially Nurses in Health Care Facilities by utilizing technological developments to increase effectiveness and efficiency. The purpose of this research is to determine the effect of mobile application empowerment educational program on nurses knowledge, attitude and competencies towards patient safety. The design of this study was purely experimental, the population was all nurses implementing the inpatient ward in 3 hospitals in Medan City (Murni Teguh Memorial Hospital, Rosiva Mother and Child Hospital and Susanna Wesley Hospital) as many as 860 nurses. Sampling was determined by the proportional random sampling method of 300 nurses. Showed that there was an increase in scores between before and after being given learning using the Mobile Application (Wilcoxon Test P value <0.001), being given learning between the intervention and control groups (Mann-Whitney Test P Value <0.001). There is an influence of the use of mobile applications (SBN Patient Safety) as a learning method on the attitudes, and competencies of respondents Multivariate ANOVA (MANOVA) test shows that all four significant values of Pillai's Trace, P Wilks' Lambda, Hotelling's Trace, Roy's Largest Root <0.001). In this study, mobile Application was well received as a learning method to improve nurses' attitudes and competencies about patient safety. It is expected that health service facilities and all related parties will maintain and improve the quality of health services by implementing patient safety as an effort to prevent patient safety incidents.